2010
DOI: 10.1089/scd.2009.0465
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell Therapy for Treatment of Cardiovascular Disease: Helping People Sooner or Later

Abstract: Despite advances in clinical management, cardiovascular disease remains the leading cause of death in America. While cardiomyocytes retain limited plasticity following maturation, the heart is grossly unable to recover from structural damage. Mesenchymal stem cell (MSC) therapy, through its promise of repair and regeneration of cardiac tissue, represents an exciting avenue of treatment for a range of cardiovascular diseases. MSCs are relatively immunoprivileged, lacking both major histocompatibility II and T-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 53 publications
1
46
0
Order By: Relevance
“…Although MSCs have been considered to be hypoimmunogenic or immunoprivileged and can escape from host immune surveillance [38], we [14] and others [15,16] have reported that MSCs activate complement in the blood, leading to cell damage and impairment of function. In our previous study [14], we focused on the direct effect of complement activation on MSC viability and function, i.e., direct MAC-mediated MSC injury, using serum as the source of complement in the absence of blood cells.…”
Section: Discussionmentioning
confidence: 77%
“…Although MSCs have been considered to be hypoimmunogenic or immunoprivileged and can escape from host immune surveillance [38], we [14] and others [15,16] have reported that MSCs activate complement in the blood, leading to cell damage and impairment of function. In our previous study [14], we focused on the direct effect of complement activation on MSC viability and function, i.e., direct MAC-mediated MSC injury, using serum as the source of complement in the absence of blood cells.…”
Section: Discussionmentioning
confidence: 77%
“…While a rapidly growing number of published reports over the last years has corroborated MSCs' potential to contribute to cell-based therapies, not only in the context of GVHD and HSCT, but also for bone and cartilage repair [184,185], cardiovascular diseases [186,187] and central nervous system disorders [188,189], the potential hazards from their use have only recently drawn scientists' attention.…”
Section: Potential Hazards From Msc Usementioning
confidence: 99%
“…MSCs are considered as a cellular substrate for the cardiac repair because of their presumptive plasticity, genetic stability, and immune tolerance (Trivedi et al, 2010). Furthermore, the accessibility, ease of handling, and enormous expansion potential of MSCs, together with their capacity for self-renewal and amenability to allogenic transplantation (Amado et al, 2005;Dai et al, 2005), provide a nearly unlimited supply of cells for therapeutic applications.…”
Section: Introductionmentioning
confidence: 99%